Nanostructured lipid carriers: An emerging platform for improving oral bioavailability of lipophilic drugs - Khan, Saba; Baboota, Sanjula; Ali, Javed; Khan, Sana; Narang, Ramandeep Singh; Narang, Jasjeet Kaur (International Journal of Pharmaceutical Investigation)
Nowadays exploration of novel lipid-based formulations is akin to a magnet for researchers worldwide for improving the in vivo performance of highly lipophilic drugs. Over the last few years, new compositions of lipids have been developed, and the probable bioavailability enhancement has been investigated. We reviewed the most recent data dealing with backlogs of conventional lipid-based formulations such as physical instability, limited drug loading capacities, drug expulsion during storage along with all the possible hindrances resulting in poor absorption of highly lipophilic drugs such as P-glycoprotein efflux, extensive metabolism by cytochrome P450 etc. In tandem with these aspects, an exclusive formulation approach has been discussed in detail in this paper. Therefore, this review focuses on resolving the concerned ambiguity with successful oral administration of highly lipophilic drugs through designing novel lipidic formulations (nanostructured lipid carriers [NLC]) that constitute a blend of solid and liquid lipids. The article highlights the potential role of such formulation in normalizing the in vivo fate of poorly soluble drugs. Finally, the present manuscript discusses the dominance of NLC over other lipid-based formulations and provides a perspective of how they defeat and overcome the barriers that lead to the poor bioavailability of hydrophobic drugs.
Keywords: Bioavailability; cytochrome P450; drug loading; in vivo performance; lipid-based formulations; lipophilic; nanostructured lipid carriers; P-glycoprotein efflux; solid-lipid nanoparticles